Life skills development and enjoyment in youth soccer: The importance of parental behaviours - Mossman, G. J.; Cronin, L. D. (Journal of Sports Sciences, 2019)
This study investigated the relationships between parental behaviours and players` life skills development and enjoyment within youth soccer. In total, 317 players (Mage = 12.83, SD = 1.70, age range = 10-16 years) completed a survey assessing parental behaviours (praise and understanding, directive behaviour, and pressure), perceived life skills development (teamwork, goal setting, time management, emotional skills, interpersonal communication, social skills, leadership, and problem solving and decision making), and enjoyment of soccer. Multiple regression analyses found that praise and understanding was the key contributor to the outcome variables, making the largest unique contribution to teamwork, goal setting, leadership, and total life skills. Directive behaviour made the largest unique contribution to emotional skills, and problem solving and decision making; whereas pressure made the largest unique contribution to participants` time management and social skills. In practice, the results suggest that parents should display praise and understanding behaviours, which were the main contributor to players` development of life skills within soccer.